Sosialisasi Pembuatan Sabun Cuci Piring dengan Inovasi Penambahan Infusa Daun Petai Cina kepada Guru-Guru di Yayasan Perguruan Islam Ummul Quro Al-Hamidiyah - Dewi Patmayuni; Erjon Erjon; Ade Arinia Rasyad; Agnes Rendowaty; Nilda Lely; Masayu Azizah; Ema Ratna Sari; Lilik Pranata; Masayu Rosyidah (Universitas Maritim AMNI Semarang, 2025)
An effective and environmentally friendly dishwashing soap is needed because conventional dishwashing soaps often contain harmful chemicals that can damage the environment. Petai cina leaves, or Moringa oleifera, have antibacterial and antioxidant properties, making them a natural choice for cleaning care. Housewives will not be separated from dishwashing soap, so the PkM team aims to Socialize the Making of Dishwashing Soap with the Innovation of Adding Petai Cina Leaf Infusion to Teachers at the Ummul Quro Al-Hamidiyah Islamic Education Foundation. The method used is education and explaining how to make it, although not all participants can make it, at least they know the process of making it, the number of participants is 15 teachers, carried out on December 19, 2024. The results of the activity showed that participants were enthusiastic about participating in the activity. After the educational activities and mentoring, teachers understood what was explained by the speaker.